Perceptions of just deserts in the context of type of offense - Gamache, Kyle (Applied psychology in criminal justice, 2019)
Preventive detention laws are intended to protect the community while providing continuing offender rehabilitation. The concept of preventive detention frequently challenges the notion of 'just desert'. With respect to civil commitment, defendants are held involuntarily for treatment beyond their sentencing. In a criminal context, defendants may be held in lieu of a criminal conviction. In the current study, we assessed the public's level of tolerance for preventive detention. We were interested in evaluating whether and to what extent a "crime hierarchy" exists for preventive detention; i.e., a perception that certain crimes are deserving of preventive detention compared to others. The results indicate that societal justifications for such confinement may stem from inherent perceptions of dangerousness rather than adherence to specific sentencing goals, political ideology, or criminal offense. This study's findings suggest that the pubic is highly tolerant of the use of preventive detention, particularly with crimes viewed as abborent or dangerous.